Assessing Health Literacy, Learning Needs, and Patient Satisfaction in Cancer Care: A Holistic Study in the Omani Context - Ayaad, Omar; Ibrahim, Rawan; AlHasni, Nabiha Said; Salman, Bushra Mustafa; Sawaya, Zeina Gaby; Al Zadjali, Razzan; Al Faliti, Balaqis; AlGhaithi, Mashan Mohammed; AlBalushi, Mohamed Hamed; AlFahdi, Amal Sulaiman; AlAwaisi, Huda Shinoon; AlBaimani, Khalid (Asian Pacific Journal of Cancer Biology, 2024)
Background: Health literacy is essential in cancer care, affecting patient outcomes, perception, and involvement in healthcare decisions. Purpose: This study aimed to evaluate and identify gaps and relationships between the levels of health literacy, learning needs, and satisfaction with educational activities among cancer patients in Oman. Methods: A cross-sectional study was conducted among 323 cancer patients at the Sultan Qaboos Comprehensive Cancer Center, University Medical City, in Muscat, Oman. Data were collected using a self-administered questionnaire, which measured health literacy using the Health Literacy Instrument for Adults (HELIA), assessed learning needs based on importance, and evaluated satisfaction with educational activities. Descriptive statistics and correlation analyses were conducted using SPSS version 23 to identify relationships between the variables. Results: The average health literacy score was 4.36, indicating a generally high level of health literacy among the participants. Learning needs were highest for chemotherapy and hormonal therapy (mean = 4.65), while satisfaction with education activities was highest for overall experience (mean = 4.38). However, there were notable gaps between the perceived importance of learning needs and satisfaction with educational activities, particularly in chemotherapy and hormonal therapy (gap = 0.46). A moderate positive correlation was found between health literacy and learning needs (r = 0.341, p = 0.022), while a stronger positive correlation existed between health literacy and satisfaction with educational activities (r = 0.58, p < 0.00001). Conclusion: Improving health literacy and addressing gaps in learning needs and educational satisfaction are crucial for enhancing cancer care outcomes and patient satisfaction in Oman.